Impact of Animated Computer-Assisted Instruction on Biology Achievement in Niger State: Post-COVID-19 Teaching Solution - Ibrahim Ismaila Kuta; C. S. Tukura; Yahaya Fatima; Fati Ali; Ndatsu, Abdulkadir (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
This research explored the impact of computer-assisted instruction (CAI) with animation on the academic performance of biology students in Niger State, designed as a post-COVID-19 strategy to enhance teaching and learning. The study utilized an experimental design, focusing on Senior Secondary II (SSII) students. Participants were selected using a simple random sampling method, which included schools, class groups, and students, resulting in two equivalent groups of 30 students each (15 males and 15 females). The instrument's reliability was verified using the PPMC formula, producing a coefficient value of 0.75. Data analysis was conducted using Analysis of Variance (ANOVA) to test the hypotheses. The results revealed that the first null hypothesis was rejected, while the second was accepted. The study highlighted that incorporating CAI with animation as a teaching aid significantly improved students' academic achievements in biology. This enhancement was attributed to the integration of traditional teaching approaches with effective instructional materials, which created a more engaging and interactive learning environment. The findings recommend implementing CAI with animation software across all senior secondary schools to boost students’ understanding and performance in biology and other science subjects. Such an approach addresses educational challenges exacerbated by the pandemic while fostering dynamic and effective learning experiences.